Philitas of Cos - Spanoudakis, Konstantinos. (Mnemosyne, Supplements, 2002)
This volume is an edition of the poetical and grammatical fragments of Philitas of Cos, the early-Hellenistic scholar and poet who served as an exemplary model for the great Alexandrian poets. His output includes frivolous Hermes and Demeter which both had fundamental impact on later metapoetic imagery, and the Ataktoi Glossai , a glossary interpreting mainly Homeric idiom in pre-Aristarchean fashion. The body of the book consists of an Introduction discussing life, literary affiliations and metre; an edition of testimonies and fragments along with a commentary elucidating matters of language and influence on the scholar-poets, Propertius and Longus. The study of Philitas is brought up to date with new testimonies and new neglected sources for the fragments. Recent papyrological findings, verse inscriptions, lexicographic sources and inscriptions from Cos are taken into consideration. Passages dubiously ascribed to Philitas are discussed. The book closes with three Appendices and comprehensive Indexes.